Pengaruh Pemberian Air Perasan Daun Salam (Syzygium polyanthum) dalam Air Minum terhadap Bobot Badan Ayam Broiler: The Effect of Bay Leaf Juice (Syzygium polyanthum) in Drinking Water on Body Weight of Broiler - Sylvina Alzari; M. Rekhnin Kamil (Jurnal Agroekoteknologi dan Agribisnis, 2022)
Broiler chicken is one type of livestock that is widely consumed to fulfil animal protein needs. Its productivity can be affected by feed. The escalating price of feed is a challenge to provide quality feed at affordable prices. The aim of the study was to analyze the effect of bay leaf juice in drinking water with different levels on body weight and feed conversion ratio (FCR) of broiler. The study was divided into 5 group of treatments regarding on differences in levels of bay leaf juice, such as P0 = control or 0%, P1 = 5%, P2 = 10%, P3 = 15% and P4 = 20%. Each treatment group consisted of 20 broiler chickens. The variable measured of this study were final body weight, and FCR. The data analysis into descriptive. There was a tendency of increased the average body weight in P1 with 5% bay leaf juice than other treatments. The FCR in the final showed that in P1 was the lower than other treatments. Utilizing of bay leaf juice in drinking water of broiler has a tendency in increased final body weight and the lower FCR.